The Effect of Employee Productivity on The Organisation: Meta-Analysis Study - Muhammad Nur; Bambang Mardi Sentosa; Andri Kurniawan (Edumaspul: Jurnal Pendidikan, 2024)
This study aims to analyze the influence between employee productivity on the organization. Employee productivity is an important factor for organizational success, and a variety of factors can affect that productivity. The source of data in the study came from an analysis of 10 national and international journals. The inclusion criteria in this study are research from SINTA and Scopus indexed journals; Research must be relevant to research variables; Research data is obtained through Google Scholar and ScienceDirect and research data attaches complete data to calculate the value of effect size. The results of the study concluded that employee productivity has a positive influence on the organization with an effect size value of 0.817; < 0.001 and z value = 5.081. These findings suggest that factors such as job stress, excessive workload, and lack of autonomy can decrease employee productivity.